(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An investigation was conducted on hospital waste management in Tangail Municipality and its impact on human health. Data was collected through questionnaire interview from local residents, superintendents, nurses, observation and secondary sources. The results revealed that wastes are collected every alternative day and though sometime in irregular basis. Hospital wastes causes different health hazards like bad smell, infestation of animals, diarrhoea, skin diseases etc. due to irregular collection, unsafe handling, disposal, storage, transportation and finally dumped with municipal wastes. For knowing health impacts, among 110 general respondents 63% was affected, and 50 respondents who were associated with medical waste handling including nurse, pickers, workers, etc. in which more than 90% were affected one or more diseases due to improper management and imposed of hospital wastes. Shortage of dustbin is common in every hospitals and clinics in Tangail Municipality. The study also revealed that 1000-1500kg wastes were generated per day in Tangail Municipal area in which 19.23% infectious and 80.77% noninfectious. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11566 J. Environ. Sci. & Natural Resources, 5(1): 121 - 127, 2012